2020
DOI: 10.1002/alz.041144
|View full text |Cite
|
Sign up to set email alerts
|

A single‐ and multiple‐ascending dose study to evaluate the safety and pharmacokinetics of oral PU‐AD, an epichaperome inhibitor to treat Alzheimer’s disease

Abstract: Background Breakdown of regulatory pathways designed to prevent aggregation and accumulation of disease‐associated proteins contributes to or causes Alzheimer’s Disease (AD). Under these conditions epichaperomes form and take control of pathological pathways. PU‐AD is a small‐molecule, orally bioavailable inhibitor specific to epichaperomes with little or no effect on normal cells, and has shown dramatic beneficial effects in animal models of AD. We describe the first‐in‐man trial of PU‐AD. Objectives This Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The majority of adverse events were reported as Grade 1 and self-limited (Silverman et al, 2020). All doses were well-tolerated in clinical subjects with no dose limiting adverse events observed (Silverman et al, 2020).…”
Section: Targeting Epichaperomesmentioning
confidence: 88%
See 2 more Smart Citations
“…The majority of adverse events were reported as Grade 1 and self-limited (Silverman et al, 2020). All doses were well-tolerated in clinical subjects with no dose limiting adverse events observed (Silverman et al, 2020).…”
Section: Targeting Epichaperomesmentioning
confidence: 88%
“…[NCT03935568]). At the 2020 AAIC meeting in San Diego it was reported that there were no serious adverse events or deaths, and no subject experienced an adverse events leading to discontinuation from the study (Silverman et al, 2020). The majority of adverse events were reported as Grade 1 and self-limited (Silverman et al, 2020).…”
Section: Targeting Epichaperomesmentioning
confidence: 99%
See 1 more Smart Citation